Development of WO3/TiO2-NT/Ti photoanode for simultaneously POME degradation, electricity generation, and hydrogen production in a photocatalysis-fuel cell system - Bachri, M. Febriansyah; Husein, Saddam; Susanto, Bambang Heru; Ratnawati, Ratnawati; Slamet, Slamet (International Journal of Renewable Energy Development, 2025)
This research presents a WO₃/TiO₂-NT/Ti photoanode for processing POME waste as well as producing electricity and hydrogen simultaneously. The photoanode in the form of nanocomposites was synthesized using an in-situ anodization method and characterized using Field Emission Scanning Electron Microscopy with Energy Dispersive X-ray (FESEM-EDX), X-ray Diffraction (XRD), Photoluminescence Spectroscopy (PL-Spectra), photocurrent transient, X-ray Photoelectron Spectroscopy (XPS), and UV-Visible Diffuse Reflectance Spectroscopy (UV-Vis DRS). The results showed that the WO₃/TiO₂-NT/Ti photoanode with 0.3 g of WO₃ precursor added during anodization exhibited the best PFC performance. The system achieved a COD degradation of 84%, hydrogen production of 11.18 mmol/m², and a maximum power density of 0.0375 mW/cm² under visible light irradiation, outperforming the variations with 0.5 g and 0.78 g WO₃ precursor. The enhanced performance was attributed to the formation of a heterojunction between WO₃ and TiO₂, as confirmed by characterization results and performance tests in COD degradation, electricity generation, and hydrogen production. Meanwhile, the addition of 0.5 g and 0.78 g WO₃ precursor reduced photocatalytic performance, likely due to excessive Na₂WO₄·2H₂O during anodization, which could partially cover the active TiO₂-NT/Ti surface and alter the electrochemical oxidation process. The developed WO₃/TiO₂-NT/Ti photoanode offers a promising solution for simultaneous wastewater treatment, clean hydrogen production, and electricity generation, with potential applications in sustainable palm oil processing industries and future renewable energy technologies.